2016
DOI: 10.3390/su8111112
|View full text |Cite
|
Sign up to set email alerts
|

Personal Water Footprint in Taiwan: A Case Study of Yunlin County

Abstract: Extreme weather events have affected the environment and water resources in Taiwan for the last two decades. Heavy rainfall, typhoons, and rising sea levels have caused severe flooding along the Southwest Coast in Taiwan. Yunlin County, an important agricultural region, will be significantly affected by climate changes, especially in coastal areas with severe land subsidence. Therefore, using the concept of the water footprint and questionnaire surveys, this study examines personal water footprints in township… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Industrial development in the township had little influence on the individual use of water. Therefore, attention on water conservation in the region was suggested to be paid to the reuse and recycling of industrial wastewater [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Industrial development in the township had little influence on the individual use of water. Therefore, attention on water conservation in the region was suggested to be paid to the reuse and recycling of industrial wastewater [17].…”
Section: Discussionmentioning
confidence: 99%
“…The high water demand in this area resulted in water-related difficulties such as water shortage and land subsidence from improper use of groundwater. Lee et al examined personal water footprint in Yunlin County and revealed that the footprint was the highest in coastal areas, mainly due to the location quotients of industries (primary, secondary, or tertiary industry) [17]. In fact, the industries also suffered from serious water shortage, especially in the dry seasons when the water rights of public and agricultural uses were prioritized over industrial uses [9].…”
Section: Study Areamentioning
confidence: 99%
“…Beverage industry's standards specify that water treated with intent for reuse must be at least the same quality as mains water [18,53]. The principle recurring activities in water treatment are shown in Table 4 [54][55][56][57][58]. Table 4.…”
Section: Water Best Practicesmentioning
confidence: 99%
“…Due to the fact that it is relatively easy to both understand and calculate, EF has become a quantitative indicator that is now widely utilized in the field of ecological economics. A number of studies conducted in Taiwan have investigated the EF model in terms of its basic concepts, theoretical hypotheses, assessment methods, deficiencies, and empirical applications [48][49][50], in addition to developing a number of EF-related theories and estimation methods. Relatedly, Lee and Peng conducted a study in 2014 [51] in which they expanded upon earlier research in order to analyze Taiwan's EF from 2008 to 2011.…”
Section: Evaluation Items Of the Ef Modelmentioning
confidence: 99%